Propene complexes of molybdenum and tungsten stabilized by intramolecular coordination of the 1-(quinol-8-yl)indenyl ligand - Mrózek, Ondřej; Dostál, Libor; Císařová, Ivana; Honzíček, Jan; Vinklárek, Jaromír (Dalton transactions (Cambridge, England, 2019)
We report herein a new class of mixed propene-indenyl complexes of molybdenum and tungsten stabilized by a strong N→M intramolecular coordination. The complexes [{η5:κN-1-(C9H6N)C9H6}(η2-C3H6)M(CO)2][BF4] (M = Mo, W) were obtained in nearly quantitative yields by the protonation of the η3-allyl ligand in compounds [(η3-C3H5){η5-1-(C9H6N)C9H6}M(CO)2] (M = Mo, W). In contrast to known η2-alkene molybdenum and tungsten compounds, the species presented here are easily isolated in the solid state. The tungsten compound [{η5:κN-1-(C9H6N)C9H6}(η2-C3H6)W(CO)2][BF4] is stable at room temperature, and its structure was unambiguously confirmed by X-ray diffraction. The reactivity of both propene complexes toward several monodentate donors was examined. In the case of dimethyl sulfide, ligand exchange takes place to afford [{η5:κN-1-(C9H6N)C9H6}M(CO)2(SMe2)][BF4] (M = Mo, W) while acetonitrile induces η5→η3 haptotropic rearrangement to give [{η3:κN-1-(C9H6N)C9H6}M(CO)2(NCMe)2][BF4] (M = Mo, W).